A Qualitative Study on the Implementation of CCTV-Based Visual Media in Enhancing Student Discipline - Festiv Zega; Adrianus Bawamenewi; Hendrikus Otniel Nasozaro Harefa; Syukur Kasieli Hulu (Jurnal Inovasi, Evaluasi dan Pengembangan Pembelajaran, 2026)
This study is motivated by the persistence of student disciplinary violations at SMK Negeri 1 Lotu, including tardiness, truancy, uniform violations, the use of mobile phones during lessons, and cheating during examinations, despite the installation of Closed-Circuit Television (CCTV) in several strategic areas. This study aims to explore the implementation of CCTV-based visual media in enhancing student discipline, identify supporting and inhibiting factors, and examine teachers’ and students’ responses to its use. A descriptive qualitative approach was employed, with data collected through observation, in-depth interviews, and documentation. The participants consisted of the principal, teachers, and students at SMK Negeri 1 Lotu. Data were analyzed through data reduction, data display, and conclusion drawing. The findings indicate that CCTV as a visual monitoring medium contributes to improving student discipline by creating a continuous supervision effect that fosters students’ awareness of school rules. The implementation is supported by the integration of CCTV monitoring with teacher supervision, institutional support, and the development of collective responsibility among school members. However, challenges such as power outages and limited camera coverage remain. Overall, both teachers and students responded positively, as CCTV-based visual media enables more objective behavioral monitoring and contributes to a safer, more orderly, and conducive learning environment.